Pembuatan Desain UI/UX dengan Metode Prototyping pada Aplikasi Layanan Pengadilan Negeri Bale Bandung menggunakan Figma - Senubekti, Mamok Andri; Dajoreyta, Geovanny Lea; Anggraini, Novita (Jurnal Informatika Terpadu, 2024)
Prototyping carried out by a UI/UX Designer is a critical element in application development. This process allows more careful planning of the application's appearance by considering user needs, making the programmer's work easier. This research case study focuses on the Bale Bandung District Court, which wants to develop an application based on improvements to the Era-Terang application. The Era-Terang application, which is designed to make it easier for the public to submit applications for certificates, still has several shortcomings. Therefore, the application developed aims to eliminate the need to physically visit the court for file delivery or registration. In this research, the prototyping method was applied using the Figma design tool. The process includes initial data collection, problem identification, creation of a usage flow, framework, sketches, and final interface design. The results of this research show that the Bale Bandung District Court Service application, which was developed using the prototyping method, succeeded in improving the quality of the user experience. This is proven through application testing, where users state that the application is easy to use and understand. Based on this user feedback, it can be concluded that the application has succeeded in fulfilling its initial objective, namely to create an easy, effective, and efficient solution for the public in accessing court services. This emphasizes the importance of a prototyping-based approach in application development, especially in increasing the accessibility and convenience of public services.